Reliability and validity of clinical tests to assess the function of the cervical spine in adults with neck pain and its associated disorders: part 5. A systematic review from the Cervical Assessment and Diagnosis Research Evaluation (CADRE) collaboration. (1st November 2020) - Lemeunier, Nadège; Suri-Chilana, Minisha; Welsh, Patrick; Shearer, Heather M.; Nordin, Margareta; Wong, Jessica J.; Torres, Paola; Oolup-da Silva, Sophia; D'Silva, Chelsea; Jeoun, Eun Been; Stern, Paula; Yu, Hainan; et al.
Abstract: The purpose of this study is to determine the reliability and validity of clinical tests used to assess cervical function, muscle strength and endurance in adults with neck pain and its associated disorders (NAD). Systematic review and update of the Bone and Joint Decade 2000–2010 Task Force on NAD. We systematically searched five electronic databases. Eligible reliability and validity studies were critically appraised using the QAREL and QUADAS-2 tools, respectively. Validity studies were ranked according to the Sackett and Haynes classification to determine clinical utility. Early studies of novel tests provide preliminary evidence, and phase III/IV studies are necessary to confirm the validity of tests in clinical practice. We conducted a best evidence synthesis. We screened 7846 citations and critically appraised 28 articles. Eighteen low risk of bias articles provide preliminary evidence of reliability and validity (phase I/II) for the cranio-cervical flexion test and deep cervical extensor (DCE) test in patients with NAD. Only two clinical tests were found to be reliable and valid. Cranio-cervical flexion test and DCE test could assess cervical muscle strength in adults with NAD. However, the evidence is supported by only phase I and II validity studies from the Sackett and Haynes classification.